RASIO SEKS DAN SEBARAN SPASIAL POPULASI GAJAH SUMATERA (Elephas maximus sumatranus) DI TAMAN NASIONAL TESSO NILO, RIAU - Nico Herlambang; Haris Gunawan; Herawati Sudoyo (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
The Sumatran  Elephant (Elephas maximus sumatranus) is one of the largest mammal and endemic species on the island of Sumatra.  It’s conservation  status  is critically endangered.  The information  about  sex ratio and spatial distribution is an important component to make a priority  in  conservation strategy. The aims  of  this  study  were  to determine sex ratio and spatial distribution of Sumatran Elephant in Tesso Nilo National Park. The multiplex PCR method was used in this study to amplify fragments SRY1 and AMELY2  on the Y chromosome and fragment  PLP1  on the X chromosome  for  sex identification in Sumatran Elephant. The analysis of spatial distribution were conducted using Arc  GIS 10.1. The result indicated that sex ratio of  Sumatran Elephant population in TNNP  is 1:3  and the  distribution of Sumatran Elephant  is generally spread outside of the region TNNP.